Effects of Seed Priming with Zinc Sulfate on Nutritional Enrichment and Biochemical Fingerprints of Momordica charantia - Shazia Anwer Bukhari; Nabila Farah; Saqib Mahmood; Javaria Altaf; Ghulam Mustafa (Journal of Food Quality)
Zinc is an essential element for plant growth and development as it plays an important role in various metabolic processes with nutritional enrichment. The treatment with zinc sulfate is also economic. Momordica charantia is an economically important medicinal plant reported for a range of pharmaceutical and pharmacological properties. In this study, nutripriming with zinc sulfate (0.1%, 0.2%, and 0.3% solution) was applied to M. charantia seeds to optimize better dose. Based upon seedling establishment, 0.3% zinc sulfate was selected for final field experiment with randomized complete block design (RCBD) with five replications. Improved germination percentage, vigor, total soluble sugars, chlorophyll-a, chlorophyll-b, total chlorophyll content, and peroxidase activity were observed variably in leaves, fruit, and peel. Other nutritive components showed maintenance in fruits of treated plants indicating that the treatment did not cause any nutritive loss. Antimicrobial activity of leaves (in terms of the minimum inhibitory concentration) against Staphylococcus aureus and Pseudomonas aeruginosa was positively correlated with sinapic acid, vanillic acid, cinnamic acid, syringic acid, chlorogenic acid, benzoic acid, and ferulic acid. It has been concluded from this study that seed priming with zinc sulfate can improve seedling establishment, photosynthetic pigments, and stable nutritive value. Therefore, zinc from zinc sulfate priming has been proved as a beneficial fertilizer for M. charantia plant growth, yield, and nutraceutical potential.